A Meta-Analysis of Price Elasticities of Transport Demand in a General Equilibrium Framework - Hans Kremers; Peter Nijkamp; Piet Rietveld (Tinbergen Institute, 2000)
Price elasticities of transport demand are an important tool toassess the impacts of pricing policies. Empirical research on these elasticitiesleads to a rather wide range of outcomes. There is obviously a need for a morerigorous methodological framework. This paper provides a new integrativeapproach to the estimation of price elasticities while taking into account anycombination of characteristics of transport demand found in various empiricalstudies. To this end, we apply meta-analysis to this set of studies. From the variousmodelling approaches that underly these studies we develop an overlappinggeneral equilibrium framework that provides a meta-regression equationrelating the price elasticity estimate to the study characteristics.
Keywords: 330